Grenzen des Ich : die Verfassung des Subjekts in Goethes Romanen und Erzählungen - Keppler, Stefan, 1973- (Quellen und Forschungen zur Literatur- und Kulturgeschichte ;, 2006)
This study treats a central complex of issues which have hitherto received little attention from Goethe scholars, namely the question of the conception and position of the subject in Johann Wolfgang von Goethe's novels and shorter narrative pieces.℗¡ In hi.